Iron- and molybdenum-repressible outer membrane proteins in competent Azotobacter vinelandii. - Page, W J (1982)
Azotobacter vinelandii produced three major proteins of 93,000, 85,000, and 81,000 daltons and a minor 77,000-dalton protein in the outer membrane of Fe-limited cells, and these cells were competent for transformation by DNA. The synthesis of these proteins was repressed in Fe-sufficient medium. Mo limitation of nitrogen-fixing cells resulted in the hyperproduction of a 44,000-dalton protein and the production of a minor 77,000-dalton protein in the outer membrane. Mo limitation enhanced competence in Fe-limited medium and induced competence in Fe-sufficient medium. The 44,000-dalton protein was replaced by a 45,000-dalton protein when Fe-sufficient medium also contained NH4+, but the cells were noncompetent. The synthesis of these proteins was repressed in Mo-sufficient medium and by NH4+ in Fe-limited medium. All of the culture supernatants contained a blue-white fluorescent material (absorbance maximum, 214 nm) which appeared to coordinate Fe3+, Fe2+, MoO4(2-), WO3(2-), and VO3(-).